METODE PROFILE MATCHING UNTUK PENENTUAN AMBALAN TERGIAT PADA GERAKAN PRAMUKA KECAMATAN JATISAMPURNA BEKASI - Muhamad Sony Pratama; Sri Dianing Asri; Desi Ramayanti; Sri Andriati Asri; Widyadi Setiawan (Universitas Teknokrat Indonesia, 2023)
DKR Jatisampurna Bekasi is a Group of Scout Members in the Jatisampurna area who are responsible for scouting management. Every year DKR Jatisampurna will choose the Most Active Ambalan in the Jatisampurna area. This study intends to get DKR Jatisampurna's active ambalan using Profile Matching. The Profile Matching method is used to compare individual/school competencies into competencies as the best shelves so that differences in competence (Gap Value) can be identified. The smaller the Gap Value generated, the greater the weighted score, which means that there is a greater opportunity for individuals/schools to become the best Troops in Jatisampurna district. The criteria provided by DKR Jatisampurna include the criteria of 35% Activeness, 35% Organizational, and 35% Non-Organizational. The three criteria are further divided into core and secondary factors, with the provisions of DKR Jatisampurna 50% core factor and 50% secondary for Activeness criteria, 60% core factor and 40% secondary for Organizational aspects, and 40% core factor and 60% secondary for non-organizational criteria. The end result of the profile matching process is the ranking of the shelves that can be used as the best shelves. Ranking is determined from the total value of the assessment sorted from the largest value to the smallest, where the alternative with the largest total value is selected as the final result. The profile matching method for determining the most active ambalan at DKR Jatisampurna Bekasi has worked well, with the highest score of 4.376875 for SMKN 14.